Benefits of Sweet Potato Leaves in Increasing Trombocite Levels in Dengue Hemorrhagic Fever Patients - Shania Evingelinda (Global Health Science Group, 2020)
Sweet potato leaves are one of the herbal plants that have pharmacological effects, including function as antioxidants, anti-genetics, anti-inflammatory and anti-cancer properties. The purpose of this literature review is to find out the benefits of sweet potato leaves on increasing platelet levels in dengue hemorrhagic fever sufferers. The method used is the literature review method from 25 Elvesier articles, StatPearls Publishing, Pubmed NCBI. Based on the results of several studies, sweet potato leaves contain several ingredients that are useful for increasing platelet levels and overcoming dengue, including flavonoid and tannin class compounds. Flavonoid and tannin class compounds have activity that increases platelets through community stimulation of GM-CSF and IL-3 which can carry megakaryocyte cell orders and have the effect of assessing the spleen.